Orchestral Pops Music: A Handbook - Manning, Lucy (Rowman & Littlefield Publishers, 2013)
In this second edition of Orchestral “Pops” Music: A Handbook, Lucy Manning brings forward to the present her remarkable compendium of information about this form of orchestral music. Since the appearance of the first edition in 2008, this work has proven critical to successful “pops” concert programming. With changes in publishers and agents, the discontinuation of the publication of certain original material or, worst of all, presses going out of business, music directors, orchestra conductors, and professional instrumentalists face formidable challenges in tracking down accurate information about this vast repertoire. This revised handbook alleviates the time-consuming task of researching these changes by offering a list of works for orchestral “pops” concerts that is comprehensive, informative, and current. Manning’s emphasis on clarity and accuracy gives users an indispensable tool for gathering vital information on the style, instrumentation, and availability of the repertoire listed, as well as notes on its performance. The user-friendly appendices include expanded instrumentation choices, easy-to-find durations, and handy title cross-references. In addition to corrections and updates, this new edition of Orchestral “Pops” Music includes at least 1,000 new title listings. Orchestral “Pops” Music: A Handbook is the ideal tool for working conductors and orchestral librarians, as well as music program directors at colleges, conservatories, and orchestras.